Boks o mistrzostwo I Ligi KS Carbo Gliwice-GKS Wybrzeże. (Gdynia : [s.n.], 1967)
Afisz inform. o meczu 19.02.1967 r.
Keywords: Boks -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne; Boks -- Polska -- 1945-1970.